Predictive Value of PLR, PNI, and HALP Scores in Ovarian Cancer Staging - Genc SO; Gulturk EA; Kurt B (Cancer Management and Research, 2025)
Serife Ozlem Genc,1 Esra Akaydin Gulturk,2 Begum Kurt1 1Department of Obstetrics and Gynecology, Sivas Cumhuriyet University Faculty of Medicine, Sivas, Türkiye; 2Department of Biostatistics, Sivas Cumhuriyet University Faculty of Medicine, Sivas, TürkiyeCorrespondence: Serife Ozlem Genc, Department of Obstetrics and Gynecology, Sivas Cumhuriyet University Faculty of Medicine, Sivas, Türkiye, Tel +90 543 456 56 24, Email drserifeozlemgenc@gmail.comPurpose: Ovarian cancer (OC) is a leading cause of gynecologic cancer mortality, where accurate staging is vital for prognosis and treatment. This study aims to evaluate the prognostic potential of the Platelet-to-Lymphocyte Ratio (PLR), Prognostic Nutritional Index (PNI), and Hemoglobin, Albumin, Lymphocyte, Platelet (HALP) scores in OC staging.Methods: The study was conducted at the Sivas Cumhuriyet University Faculty of Medicine, Department of Obstetrics and Gynecology, between January 1, 2009, and December 31, 2021. A total of 96 OC patients were retrospectively analyzed. Preoperative PLR, PNI, and HALP scores were calculated from routine laboratory parameters. Associations between these scores and clinicopathological factors, including OC stage, were evaluated. The discriminatory power of each index was assessed through ROC curve and AUC (area under the curve) analysis.Results: The AUC for PLR was 0.689 (p < 0.05), indicating significant prognostic value, while the HALP score showed an AUC of 0.671 (p < 0.05). Both markers were significantly associated with OC stages, with higher PLR and lower HALP scores correlating with advanced stages. In contrast, PNI demonstrated a lower AUC of 0.398 (p > 0.05), indicating limited prognostic utility.Conclusion: PLR and HALP scores are useful prognostic markers for OC staging, offering cost-effective and accessible tools in clinical practice. PNI, however, was less predictive. These findings suggest that PLR and HALP could complement existing staging methods, aiding in clinical decision-making. Future large-scale studies are warranted to validate these results.Keywords: HALP score, PNI, ovarian cancer, prognostic markers